1999
DOI: 10.1016/s0891-5849(98)00308-6
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum-induced oxidative events in cell lines: glioma are more responsive than neuroblastoma

Abstract: Abstract-Aluminum, a trivalent cation unable to undergo redox reactions, has been linked to many diseases such as dialysis dementia and microcytic anemia without iron deficiency. It has also been implicated in Alzheimer's disease although this is controversial. Because cell death due to oxidative injury is suspected to be a contributory factor in many neurological diseases and aluminum neurotoxicity, glioma (C-6) and neuroblastoma (NBP 2 ) cells were utilized to assess early changes in oxidative parameters con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 23 publications
(24 reference statements)
1
35
0
1
Order By: Relevance
“…Previous research has indicated that oxidative stress has an important role in aluminium toxicity (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In accordance with this is the hypothesis by Joshi (5) that aluminium interferes with iron ions, particularly with trivalent iron ions which participate in oxidoreduction.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Previous research has indicated that oxidative stress has an important role in aluminium toxicity (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In accordance with this is the hypothesis by Joshi (5) that aluminium interferes with iron ions, particularly with trivalent iron ions which participate in oxidoreduction.…”
Section: Discussionmentioning
confidence: 64%
“…Recent data indicate that decreased erythrocyte delta-aminolevulinate dehydratase activity in haemodialysed patients with increased aluminium levels is related to the oxidation of sulfhydryl groups (4). The last few decades have Brought to you by | MIT Libraries Authenticated Download Date | 5/9/18 8:02 AM seen increasing evidence that oxidative stress has an important role in aluminium toxicity (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Therefore, the aim of this study was to examine lipid peroxidation and the activity of antioxidative enzymes in erythrocytes of workers occupationally exposed to aluminium.…”
mentioning
confidence: 99%
“…It was discovered in a previous study that the amyloid plaques are surrounded by glial reactive cells, Thus, exposition to Al can activate the oxidative processes of glial cells, which in turn can indirectly damage the neurons integrity (13) .…”
Section: Inmentioning
confidence: 99%
“…Zaman (1994) showed that Al stimulates NADPH oxidation and takes part in the process of free radical formation. Experimental animal models and cell culture studies reveal that aluminium affects the expression of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase and glutathione (GSH) possibly leading to membrane fragility as a consequence (Julka and Gill, 1996;Oteiza et al, 1993;Campbell et al, 1999). These data support the role of oxidative stress in aluminium induced cellular dysfunction and if this is indeed the case, antioxidants, such as selenium, may be protective.…”
Section: Introductionmentioning
confidence: 87%